The Halloysite Clays of Northland, New Zealand (8b1b7779-6b27-407c-8df6-0530480970df) - Townsend MG; Evans RB (The Australasian Institute of Mining and Metallurgy, 1990)
In Northland, New Zealand, localised large deposits of halloysite clay have been produced by in-situ alteration of rhyolite volcanics of Pliocene or Pleistocene age, which were erupted through pre- Pliocene sedimentary strata and locally through Pleistocene basalt; and which were subsequently onlapped by further basalt flows. Alteration to clay has been a result of both hydrothermal and of meteoric processes, and decreases in intensity of alteration with increasing depth.The raw material is crushed and fractionated to produce a product of less than 2 micron particle size, which is of exceptional whiteness and brightness. The unique properties of the clays render them highly desirable for specialised ceramic purposes.